Portfolio efficiency analysis with SFA: the case of PSI-20 companies - Ferreira, N. B.; Oliveira, M. M. (Applied Economics, 2016)
This study aimed to assess the technical efficiency (TE) of individual companies and their respective sectors that are traded on the Portuguese stock market. We accomplished this by combining the internal input variables (e.g., ‘market value and return’) with exogenous variables (e.g., ‘interest income’, ‘depreciation’, ‘cost of goods’, ‘employees’ and ‘net sales’) into a Stochastic Frontier Analysis (SFA) model. The TE of the PSI-20 (Portuguese Stock Index) was estimated using factors that affect efficiency variability. The main advantage of using the SFA approach is its potential to discriminate between measurement error and systematic inefficiencies in the estimation process. The results demonstrated that TE is higher for enterprises in the industrial, construction and distribution sectors, whereas the commercial banking sector has the lowest TE scores. The ‘employees’ and ‘depreciation’ are the variables which most contribute to stock market inefficiency.